PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER PADA MATERI SALING KETERGANTUNGAN DALAM EKOSISTEM DI KELAS VII MTs NEGERI TANAH JAWA T.P 2014/2015 - Winda Afriza, Afni; Rosenta Purba, Ika (Jurnal Metabio, 2022)
This study aims to determine differences in student learning outcomes using the Numbered Heads Together learning model. This research is an experimental study with a pre-test, post-test design. The population was 203 students, and the sample size was 80 students (Cluster Random Sampling). Class VII-2 served as the experimental class, and class VII-4 as the control class. Data analysis was conducted by calculating the average score and standard deviation, and hypotheses were tested using the t-statistic or t-test at a significance level of α = 0.05. The average pre-test score for the experimental class was 44.25, and the average post-test score for the experimental class was 78.37. The average pre-test score for the control class was 38.50, and the average post-test score for the control class was 65.25. This indicates an improvement in the topic of interdependence in ecosystems in class VII of MTs Negeri Tanah Jawa in the 2014/2015 academic year, with a score of 34.12. The results of the hypothesis test using the t-test obtained a calculated t (7.68) > t table (2.00), therefore H0 is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using the Numbered Heads Together learning model on interdependence in ecosystems in grade VII MTs Negeri Tanah Jawa in the 2014/2015 academic year. It was concluded that there is a significant difference in learning outcomes using the Numbered Heads Together learning model on interdependence in ecosystems in grade VII MTs Negeri Tanah Jawa in the 2014/2015 academic year.